A tool for the visualisation of public opinion. (23rd December 2013) - Soulis, Konstantinos; Varlamis, Iraklis; Giannakoulopoulos, Andreas; Charatsev, Filippos
The rise in popularity of the web and social media has significantly changed the way voters communicate and form their opinions. National governments are also affected by the hype of social media, so they launch new debate tools and open social platforms where citizens are able to communicate, collaborate and exchange opinions. When the amount of opinions increases, then it becomes difficult to process and interpret them manually. In this case, opinion–mining techniques and information visualisation tools can be employed to depict the public opinion and give comprehensive visual summaries. In this work, we present an information visualisation tool for surveys, which allows users to select from a variety of graphs, drill down to selected periods or roll–up to a larger scale and supports input from both closed–end and open–end questions. In the latter case, the tool employs opinion–mining techniques to quantify voter's opinion.